2010
DOI: 10.1021/es102362t
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Dissolved Organic Matter Fluorescence in Aquatic Environments: An Interlaboratory Comparison

Abstract: The fluorescent properties of dissolved organic matter (DOM) are often studied in order to infer DOM characteristics in aquatic environments, including source, quantity, composition, and behavior. While a potentially powerful technique, a single widely implemented standard method for correcting and presenting fluorescence measurements is lacking, leading to difficulties when comparing data collected by different research groups. This paper reports on a large-scale interlaboratory comparison in which natural sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
339
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 615 publications
(359 citation statements)
references
References 37 publications
3
339
1
Order By: Relevance
“…Three recent publications from NIST researchers have particular significance for EEM correction, including a reference to the recently released ASTM standard guide (E2719) for fluorescence calibration and correction [9], a reference to CDOM EEMs and all aspects of instrument and IFE correction, [2] and a reference to the validation of the Fluorolog ® as the true accurate fluorometer for its use in generating and validating a series of Standard Reference Materials [7]. Furthermore, a recent paper has been accepted outlining the results of a major international interlaboratory comparison for CDOM IHSS standard samples; this study was headed by researchers and the United States Geological Survey (USGS), and was the focused outcome of a recent 2008 Chapman conference sponsored by the American Geophysical Union [8]. In terms of potential applications of CDOM analysis two reviews of the literature exist of note, including one paper explaining the potential of CDOM for monitoring all stages of water-recycling [14], and another focusing on analysis of natural and wastewater sources [1].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three recent publications from NIST researchers have particular significance for EEM correction, including a reference to the recently released ASTM standard guide (E2719) for fluorescence calibration and correction [9], a reference to CDOM EEMs and all aspects of instrument and IFE correction, [2] and a reference to the validation of the Fluorolog ® as the true accurate fluorometer for its use in generating and validating a series of Standard Reference Materials [7]. Furthermore, a recent paper has been accepted outlining the results of a major international interlaboratory comparison for CDOM IHSS standard samples; this study was headed by researchers and the United States Geological Survey (USGS), and was the focused outcome of a recent 2008 Chapman conference sponsored by the American Geophysical Union [8]. In terms of potential applications of CDOM analysis two reviews of the literature exist of note, including one paper explaining the potential of CDOM for monitoring all stages of water-recycling [14], and another focusing on analysis of natural and wastewater sources [1].…”
Section: Resultsmentioning
confidence: 99%
“…2A) for a CDOM sample involves scanning the excitation wavelength from 240-500 nm and acquiring the emission spectra from 250-600 nm. Spectral-bandpass and resolution conditions are now generally accepted to be 5 nm by the research community [8]. Because the excitation axis is scanned and the excitation source exhibits wavelength-dependent intensity features, the emission detector signal must be divided by the respective excitation-source intensity monitored using the reference (R) detector at each excitation coordinate.…”
Section: An Overview Of the Methods Of Excitation-emission Mapping Witmentioning
confidence: 99%
See 2 more Smart Citations
“…0.2 μm) and stored refrigerated in dark coloured bottles. An inter-laboratory study [61] indicated that short term storage (<2 months) presented no significant storage issues, although this is dependent on the origin of the samples and its susceptibility to bacterial regrowth. 2.…”
Section: Sample Handling Recommendationsmentioning
confidence: 99%